Diseño y elaboración de órtesis funcionales de bajo costo para perros domésticos (canis lupus familiaris) con parálisis de las extremidades posteriores en la clínica veterinaria San Andrés. - Mayorga Moreta, Lizeth Alejandra (2021)
This research project aimed to design and develop an orthosis for dogs with hind limb paralysis in order to improve the lifestyle of pets and to make pet owners aware that there is another solution such as the help of an orthosis, avoiding the cheapest solution such as euthanasia and abandonment of dogs leaving them with an uncertain future. Animal welfare is taken into consideration to live a full and healthy life, that is to say, with a good state of health and mobility in acceptable conditions, when an illness or permanent or transitory disability arrives, animal welfare does not change, they are relatively the same, the recovery of a permanent disability by means of the use of an orthosis is a necessity. For the elaboration of the orthosis we searched for materials that are appropriate, economical and above all accessible, that are related to the anatomy of each dog for the support of their hind limbs and spine. The orthosis elaborated in this project fulfills all the functions and its purpose is to help the lost or diminished motor function as a support, giving the dog a quality of life and giving the owners the satisfaction of seeing their dog having its independence. To reach this result, we analyzed the needs of obtaining an orthosis and the different problems that cause paralysis in the hind limbs, which were solved with the elaboration of the orthosis, avoiding problems in their skin due to the need to mobilize themselves, which makes them drag their hind limbs. In this way we created awareness about the importance of care and being able to provide a dignified life to the canines, since they are the ones that give us their company and that is why they need our attention and care.